Enforcement and compliance in Lima's street markets: the origins and consequences of policy incoherence toward informal traders - Sally Roever (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2005)
Almost twenty years have passed since researchers from the Institute for Liberty and Democracy in Peru showed how `bad laws' impose disproportionate costs on those who choose formality. Although a multitude of conflicting regulations still precludes effective governance of informal trade in Lima, this paper argues that the sources of those conflicts are more diverse – though perhaps more tractable – than they might have been twenty years ago. Specifically, the paper identifies three sources of policy incoherence in Lima that contribute to persistent clashes between informal workers and policy makers: (1) the lack of definitional clarity in national and metropolitan-level legislation; (2) the absence of reliable mechanisms designed to resolve those definitional contradictions; and (3) a resulting lack of policy continuity over time within individual municipal administrations.
Keywords: E26; H71; I38; K42; 330; informal economy; taxation; law; government policy; Informeller Sektor; Ambulanter Handel; Lima